Politik Identitas dan dan penguatan Demokrasi Lokal (Kekuatan Wong kito dalam demokrasi lokal) - sirajudin fikri (Fakultas Adab dan Humaniora UIN Raden Fatah, 2018)
This paper examines how the Palembang local community uses local values as a process of strengthening democracy. The study in this paper discusses what values still exist and are still used in everyday life, whether they are used in conscious or local values that they actually use but they are not aware of that. There is no previous research that specifically addresses the existence of local values of Wong Kito in everyday life, and this is deepened in the realm of democratization in the local sphere. Researchers felt it was important to conduct this research on the basis of several reasons, none of which previously examined local politics, especially democratization held by indigenous people of Palembang, the second reason is whether this zero conflict occurred in Palembang because they still use local values in their daily lives -day, there are a number of questions in this study, but can be pursued as follows, what local values are still being used, and can they increase the sense of unity and unity in the community ?. This study uses a type of qualitative research and case study approach, in order to direct research to be organized and planned well and systematically. The findings in the study are that there are several local values that are still used and are still a reference for the community in the process, daily life such as peddling, charity, celebration, mutual cooperation, ngobeng. This value is believed to still be a tool / weapon to reduce all problems in the community. Then, local values are still believed to be a means of unifying how the stakeholders, especially the executive and the legislature, show their role, especially in issuing policies, because the policy or legal umbrella is the most appropriate realization to be issued. Keywords: local value, Palembang, local democracy